The impact of stratifying by family history in colorectal cancer screening programs. Issue 5 (20th February 2015) - Goede, Simon Lucas; Rabeneck, Linda; Lansdorp‐Vogelaar, Iris; Zauber, Ann G.; Paszat, Lawrence F.; Hoch, Jeffrey S.; Yong, Jean H.E.; van Hees, Frank; Tinmouth, Jill; van Ballegooijen, Marjolein
<x xml:space="preserve">Abstract</x> In the province‐wide colorectal cancer (CRC) screening program in Ontario, Canada, individuals with a family history of CRC are offered colonoscopy screening and those without are offered guaiac fecal occult blood testing (gFOBT, Hemoccult II). We used microsimulation modeling to estimate the cumulative number of CRC deaths prevented and colonoscopies performed between 2008 and 2038 with this family history‐based screening program, compared to a regular gFOBT program. In both programs, we assumed screening uptake increased from 30% (participation level in 2008 before the program was launched) to 60%. We assumed that 11% of the population had a family history, defined as having at least one first‐degree relative diagnosed with CRC. The programs offered screening between age 50 and 74 years, every two years for gFOBT, and every ten years for colonoscopy. Compared to opportunistic screening (2008 participation level kept constant at 30%), the gFOBT program cumulatively prevented 6, 700 more CRC deaths and required 570, 000 additional colonoscopies by 2038. The family history‐based screening program increased these numbers to 9, 300 and 1, 100, 000, a 40% and 93% increase, respectively. If biennial gFOBT was replaced with biennial fecal immunochemical test (FIT), annual Hemoccult Sensa or five‐yearly sigmoidoscopy screening, both the added benefits and colonoscopies required would decrease. A biennial gFOBT screening program that identifies individuals with a family history of CRC and recommends them to undergo colonoscopy screening would prevent 40% (range in sensitivity analyses: 20–51%) additional deaths while requiring 93% (range: 43–116%) additional colonoscopies, compared to a regular gFOBT screening program.